The Effect of the Picture and Picture Model Assisted by the TikTok Application on Procedural Text Writing Skills - Melati Fitri Insani; Deden Ahmad Supendi; Tanti Agustianti (Raja Zulkarnain Education Foundation, 2026)
This study aims to determine the effect of the Picture and Picture learning model assisted by the TikTok application on the procedural text writing skills of ninth-grade students at SMP Negeri 1 Jampang Tengah. This study was conducted based on the fact that students' low ability to compose procedural texts using sequential steps according to the text structure, inappropriate use of linguistic rules, and low student participation in writing lessons. This study used an experimental method with a posttest-only control group design. The study population was all ninth-grade students of SMP Negeri 1 Jampang Tengah in the 2025/2026 academic year who participated in procedural text writing skills learning using Picture and Picture assisted by the TikTok application. The study sample consisted of two classes: class IX B as the experimental class and class IX C as the control class, each with 28 students. The research instruments were a procedural text writing test and a learning observation sheet. Learning in the experimental class was carried out through the presentation of images on TikTok as stimuli, activities to sort images based on the Picture and Picture model, group discussions, and practice writing procedural texts. Meanwhile, the control class received conventional learning. Data were analyzed using the nonparametric Mann–Whitney U statistical test because the posttest data were not normally distributed. The results showed that the average procedural text writing skill score for the experimental class was 82.75, while the control class was 61.42. The Mann–Whitney U test results showed a significance value of 0.000 < 0.05, indicating a significant difference between the two classes. Thus, the Picture and Picture learning model assisted by the TikTok application has a significant effect on procedural text writing skills.